COVID-19: Lessons on malnutrition, nutritional care and public health from the ESPEN-WHO Europe call for papers. Issue 12 (December 2022) - Barazzoni, Rocco; Breda, Joao; Cuerda, Cristina; Schneider, Stephane; Deutz, Nicolaas E.; Wickramasinghe, Kremlin; ,; Abbasoglu, Osman; Beurskens Meijerink, Judith; Bischoff, Stephan; Burgos Pelaez, Rosa; Cardenas, Diana; et al.
Summary: With prolonged pandemic conditions, and emerging evidence but persisting low awareness of the importance of nutritional derangements, ESPEN has promoted in close collaboration with World Health Organization-Europe a call for papers on all aspects relating COVID-19 and nutrition as well as nutritional care, in the Society Journals Clinical Nutrition and Clinical Nutrition ESPEN. Although more COVID-related papers are being submitted and continue to be evaluated, ESPEN and WHO present the current editorial to summarize the many published findings supporting major interactions between nutritional status and COVID-19. These include 1) high risk of developing the disease and high risk of severe disease in the presence of pre-existing undernutrition (malnutrition) including micronutrient deficiencies; 2) high risk of developing malnutrition during the course of COVID-19, with substantial impact on long-term sequelae and risk of long COVID; 3) persons with obesity are also prone to develop or worsen malnutrition and its negative consequences during the course of COVID-19; 4) malnutrition screening and implementation of nutritional care may improve disease outcomes; 5) social and public health determinants contribute to the interaction between nutritional status and COVID-19, including negative impact of lockdown and social limitations on nutrition quality and nutritional status. We believe the evidence supports the need to consider COVID-19 as (also) a case of malnutrition-enhanced disease and disease-related malnutrition, with added risk for persons both with and without obesity. Similarities with many other disease conditions further support recommendations to implement standard nutritional screening and care in COVID-19 patients, and they underscore the relevance of appropriate nutritional and lifestyle prevention policies to limit infection risk and mitigate the negative health impact of acute pandemic bouts.